Development of a framework to improve the utilisation of malaria research for policy development in Malawi - Chikondi Mwendera; Christiaan de Jager; Herbert Longwe; Charles Hongoro; Kamija Phiri; Clifford M. Mutero (BMC, 2017)
Abstract Background The existing gap between research evidence and public health practice has attributed to the unmet Millennium Development Goals in Africa and consequently, has stimulated the development of frameworks to enhance knowledge translation. These efforts aim at maximising health research utilisation in policy and practice to address the world's disease burdens, including malaria. This study aimed at developing a contextual framework to improve the utilisation of malaria research for policy development in Malawi. Methods The study used two approaches including: two case studies of policy analysis exploring the policy-making process in Malawi, utilisation of local malaria research, and the role of key stakeholders in policy formulation process; and the assessment of facilitating factors and barriers to malaria research utilisation for policy-making in Malawi. Results From the case studies' lessons and elements identified during the assessment of facilitating factors and barriers, a framework is developed to promote an integrated approach to knowledge translation. In this framework the Ministry of Health is considered as the main user of knowledge from research through the demand created by the research directorate and the National Malaria Control Programme. Key documents identified as being particularly relevant to the Ministry of Health for purposes of knowledge translation include the National Health Research Agenda, Guidelines for Policy Development and Analysis, and Guidelines for Evidence Use in Policy-making. Institutions conducting academic and policy-relevant malaria research in Malawi are identified and a consolidation of their linkages with the users of research is established through the Knowledge Translation Unit, the Evidence Informed decision-making Centre, and the African Institute for Development Policy. Equally, key players in this framework are the funding partners for both research and programmes that need to see accountability and impact of their support. Independent advisors, partners, and consultants also have their vital role in the process. Conclusion The framework offers a practical basis for the factors identified and their linkages to promote a co-ordinated approach to malaria research utilisation in policy-making. Its applicability and success hinges on its wider dissemination and ownership by the government through the National Malaria Control Programme.